Pengaruh Tax Planning, Profitabilitas, Dan Inventory Intensity Terhadap Tax Avoidance - Delsa Nafhilla (Yayasan Literasi Ilmiah Indonesia, 2022)
This study aims to examine the effect of Tax Planning, Profitability, Inventory Intensity on Tax Avoidanc Data were analyzed using SPSS 22. This study uses a sample of manufacturing companies listed on the Indonesian Stock Exchange in 2016-2020 based on criteria established by the author, so that those who meet the criteria. The research technique used multiple linear analysis and analysis of absolute differences. The results show that tax planning, Profitability, inventory intensity have a positive effect on tax avoidance.